Effects of Carbon Pricing and Other Climate Policies on CO₂ Emissions - Emanuel Kohlscheen; Richhild Moessner; Elod Takáts (Center for Economic Studies and ifo Institute (CESifo), 2021)
We provide ex-post empirical analysis of the effects of climate policies on carbon dioxide emissions at the aggregate national level. Our results are based on a comprehensive database of 121 countries. As climate policies we examine carbon taxes and emissions trading systems (ETS), as well as the overall stringency of climate policies. We use dynamic panel regressions, controlling for macroeconomic factors such as economic development, GDP growth, urbanisation, as well as the energy mix. We find that higher carbon taxes and prices of permits in ETS reduce carbon emissions. An increase in carbon taxes by 10 per ton of CO2 reduces CO2 emissions per capita by 1.3% in the short run and by 4.6% in the long run.
Keywords: O44; Q00; Q48; Q58; Q40; Q50; 330; climate policies; carbon tax; carbon emission trading system; carbon dioxide; climate change; emissions; energy; environment; growth